Dynamic lightpath establishment in wavelength routed WDM networks. - Zang, Hui (IEEE Communications magazine)
In wavelength-routed WDM networks, a control mechanism is required to set up and take down all-optical connections. Upon the arrival of a connection request, this mechanism must be able to select a route, assign a wavelength to the connection, and configure the appropriate optical switches in the network. The mechanism must also be able to provide updates to reflect which wavelengths are currently being used on each link so that nodes may make informed routing decisions. In this work, we review control mechanisms proposed in the literature. We also investigate and compare two different distributed control mechanisms for establishing all-optical connections in a wavelength-routed WDM network: an approach based on link-state routing, and one based on distance-vector routing